Education Management: Implications of Information Technology Development on The Moral Formation of Adolescents - Suban, Alwan; Ilham, Ilham (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to determine the implications of Islamic education management in developing information technology for forming adolescent morals. This research is a descriptive type of field research using qualitative methods. The results of this study indicate the various impacts of technological sophistication on the moral behavior of students today so that attention and supervision from various parties are needed so that the following development process does not cause bad things. Supervision from parents, and the surrounding community, holding positive activities involving teenagers, as well as attention and supervision from parents towards students must be more significant and closer to them so that they are more open and easy to direct So that one of the efforts that the education management must take is to combine information technology with human resources. In addition to socializing on how to use technology media, they must provide socialization about the limitations that must be applied by each student so that they are not excessive in using technology media and do not take advantage of information that can damage morale.